Preliminary assessment of underground hydrogen storage sites in Ontario, Canada. (7th June 2019) - Lemieux, Alexander; Sharp, Karen; Shkarupin, Alexi
Abstract: The replacement of coal-fired power plants with increasing proportions of renewable and nuclear energies in the province of Ontario highlights the need to balance seasonal energy demands. This can be achieved through power-to-gas technology, where excess energy is used to generate hydrogen gas through electrolysis, and the generation is coupled with underground hydrogen storage. This article presents a preliminary assessment regarding the potential for underground hydrogen storage in geological formations including salt and hard rock caverns, depleted oil and gas fields, and saline aquifers in Ontario, highlighting potential locations where future storage could be feasible. Southern Ontario presents many potential storage options, including Silurian bedded salts, depleted Ordovician natural gas reservoirs, saline aquifers in Cambrian sandstone and hard rock caverns in argillaceous limestones. Hard rock caverns in Precambrian crystalline rocks of the Canadian Shield are also discussed, in addition to the potential for the use of lined rock caverns. This work aims to provide a basis for further research regarding the appropriate location of underground hydrogen gas storage facilities in Ontario. Highlights: The bulk of Ontario's energy supply is provided by wind or nuclear energy. The prevalence of these energies result in periods of surplus energy supply. This surplus energy can be stored as hydrogen gas to buffer supply and demand. Underground storage in geological media is explored for Ontario. This article considers salt or hard rock caverns, petroleum reservoirs, and aquifers.